Just Literature Philosophical Criticism and Justice. - Zamir, Tzachi, 1967- (Milton : Routledge, 2019)
In Just Literature, Tzachi Zamir introduces the idea of 'philosophical criticism' as an innovative approach to interpreting literary texts. Throughout the book, Zamir uses the theme of justice as a case study for this new critical approach. By using philosophical criticism', Zamir posits that a stronger grasp of the idea of justice can increase one's understanding of literature, and thus its value. He offers philosophical readings of works by Dante, Shakespeare, Toni Morrison, J. M. Coetzee and Philip Roth to explore the relationship between aesthetic and epistemic value. Zamir argues that, while literature and philosophy remain separate entities, examining the two in tandem may help inform the study of both. Offering an inventive twist on an established dynamic, this book is essential reading for any student or scholar of literature or philosophy.
Description based upon print version of record.
OCLC-licensed vendor bibliographic record.
Keywords: Justice in literature; LITERARY CRITICISM / General